Buckling and vibration behaviour of syntactic foam core sandwich beam with natural fiber composite facings under axial compressive loads. (15th October 2019) - Waddar, Sunil; Pitchaimani, Jeyaraj; Doddamani, Mrityunjay; Barbero, Ever
Abstract: An experimental study of buckling and dynamic response of cenosphere reinforced epoxy composite (syntactic foam) core sandwich beam with sisal fabric/epoxy composite facings under compressive load is presented. Influence of cenosphere loading and surface modification on critical buckling load and natural frequencies of the sandwich beam under compressive load is presented. The critical buckling load is obtained from the experimental load-deflection data while natural frequencies are obtained by performing experimental modal analysis. Results reveal that natural frequencies and critical buckling load increase significantly with fly ash cenosphere content. It is also observed that surface modified cenospheres enhance natural frequencies and critical buckling load of the sandwich beam under compressive load. Vibration frequencies reduce with increase in compressive load. Fundamental frequency increases exponentially in post-buckling regime. Experimentally obtained load-deflection curve and natural frequencies are compared with finite element analysis wherein results are found to be in good agreement.